The Combined Effects Of Some Abiotic Factors And Nutrient Conditions On The Growth And Biochemical Composition Of Four Selected Marine Diatoms, Isolated From Penang National Park Coastal Waters - Alsull, Mohamed Mohamed (2013)
In this study, four marine diatoms Nitzschia panduriformis W. Gregory; Nitzschia lorenziana Grunow; Cylindrotheca closterium (Ehrenberg) and Navicula distans (W. Smith), were isolated from water samples collected from eight stations located around the coastal waters of Penang National Park. Identification of the isolated species was carried out based on the morphological and fine characteristics of the frustules observed under SEM, as well as amplifying of specific region of the DNA using Polymerase Chain Reaction (PCR) molecular technique. . The isolated species were studied under varied culture conditions; temperature 5, 15 and 26 ±1˚C; salinity 6, 13 and 27±1‰; light duration 12:12 h light: dark cycle and 24 h continuous light; various nitrogen and phosphorus concentrations (free N and P media, 90% reduction, 50 reduction and full strength media 100%) using F/2 media as a growth medium. The effects of fluctuation in these culturing conditions were investigated on the growth kinetic, growth rate (d -1), chlorophyll a content (μgmL-1), dry weight (mgL-1) and the biochemical composition including total lipid, carbohydrate and protein content as percentage of the dry weight (%) Among the four diatoms tested, Nitzschia panduriformis and Navicula distans recorded the highest growth rate (0.63 and 0.61 d -1 respectively); while the growth rate of Nitzschia lorenziana never exceeded 0.44 d -1 under optimum growth conditions.